Therapeutic Potential of the Cyclin-Dependent Kinase Inhibitor Flavopiridol on c-Myc Overexpressing Esophageal Cancer - Hassan, Md Sazzad; Cwidak, Nicholas; Johnson, Chloe; Däster, Silvio; Eppenberger-Castori, Serenella; Awasthi, Niranjan; Li, Jun; Schwarz, Margaret A.; von Holzen, Urs (Frontiers in Pharmacology, 2021)
Tumors with elevated c-Myc expression often exhibit a highly aggressive phenotype, and c-Myc amplification has been shown to be frequent in esophageal cancer. Emerging data suggests that synthetic lethal interactions between c-Myc pathway activation and small molecules inhibition involved in cell cycle signaling can be therapeutically exploited to preferentially kill tumor cells. We therefore investigated whether exploiting elevated c-Myc expression is effective in treating esophageal cancer with the CDK inhibitor flavopiridol. We found frequent overexpression of c-Myc in human esophageal cancer cell lines and tissues. c-Myc overexpression correlated with accelerated esophageal cancer subcutaneous xenograft tumor growth. Esophageal cancer cells with elevated c-Myc expression were found preferentially more sensitive to induction of apoptosis by the CDK inhibition flavopiridol compared to esophageal cancer cells with lower c-Myc expression. In addition, we observed that flavopiridol alone or in combination with the chemotherapeutic agent nanoparticle albumin-bound paclitaxel (NPT) or in combinations with the targeted agent BMS-754807 significantly inhibited esophageal cancer cell proliferation and subcutaneous xenograft tumor growth while significantly enhancing overall mice survival. These results indicate that aggressive esophageal cancer cells with elevated c-Myc expression are sensitive to the CDK inhibitor flavopiridol, and that flavopiridol alone or in combination can be a potential therapy for c-Myc overexpressing esophageal cancer.